Prevalence, correlates and trends in seroadaptive behaviours among men who have sex with men from serial cross-sectional surveillance in San Francisco, 2004–2011. (31st March 2014) - Snowden, Jonathan M; Wei, Chongyi; McFarland, Willi; Raymond, H Fisher
Abstract : Objectives: We sought to assess the prevalence and correlates of seroadaptive behaviours (ie, sexual history incorporating some unprotected anal intercourse (UAI)) and conventional risk reduction behaviours (ie, consistent condom use or no anal intercourse) among men who have sex with men (MSM) in San Francisco in 2011. We compared the prevalence of seroadaptive behaviours between serial cross-sectional surveys from 2004, 2008 and 2011. Methods: We analysed data from the 2011 wave of the National HIV Behavioral Surveillance system in San Francisco. We categorised men's self-reported sexual behaviour history in the past 6 months into a schema of seroadaptive behaviours and conventional risk reduction behaviours. We compared the prevalence of behaviour categories by self-reported HIV serostatus, HIV testing history, awareness of pre-exposure HIV prophylaxis (PrEP) and diagnosis of a sexually transmitted infection (STI). Results: Seroadaptive behaviours remained common in San Francisco MSM, with a 2011 prevalence of 46.6%, up from 35.9% in 2004. Consistent condom use or no anal intercourse was more common than seroadaptive behaviours in HIV-negative MSM, men who had not heard of PrEP and men without an STI diagnosis. Seroadaptive behaviours increased from 2004 to 2011. Conclusions: HIV seroadaptive behaviours remain common in San Francisco MSM, have increased in the last decade and are practiced differently by MSM with different sexual health knowledge and outcomes. Public health researchers and officials should continue to document the prevalence, intentionality, efficacy and safety of seroadaptive behaviours among diverse communities of MSM.